Brief Report: Pharmacokinetic/Pharmacodynamic Investigation of Single-Dose Oral Maraviroc in the Context of HIV-1 Pre-exposure Prophylaxis. (1st November 2016) - Fox, Julie; Tiraboschi, Juan M.; Herrera, Carolina; Else, Laura; Egan, Deirdre; Dickinson, Laura; Jackson, Akil; Olejniczak, Natalia; Back, David; Khoo, Saye; Shattock, Robin; Boffito, Marta
Abstract : Abstract: To investigate the pharmacokinetics/pharmacodynamics of single-dose maraviroc 300 mg in HIV-1 exposure compartments. Maraviroc concentrations in blood, secretions (vaginal, urethral, oral, and rectal), and tissue (vaginal and rectal) were measured, and ex vivo challenge was performed in 54 healthy volunteers to study protection from HIV infection. Maraviroc Cmax occurred within 4 hours in most compartments. Concentrations from 4 to 72 hours were above intracellular (IC) IC90 in all compartments, range 15–8095 ng/mL. Mean AUC0-72 compartment-to-plasma ratios were highest in the rectum (45–819) and urethra (144) compared with the female genital tract (1.6–4.8) and saliva (0.2). No sex differences in AUC0-72 or Cmax were observed. No ex vivo protection from HIV-1BaL occurred in rectal or vaginal tissue. Despite high and sustained concentrations, single-dose maraviroc was not protective against ex vivo challenge of vaginal/rectal tissue. Abstract : Supplemental Digital Content is Available in the Text.